2010
DOI: 10.4236/health.2010.25069
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: <i>Effect of aerobic training on airflow obstruction, vo2 max, EIB in stable asthmatic children</i>

Abstract: Journal:Health ( Free style text with summary of information from above and more details that can not be expressed by ticking boxes.This article has been retracted to straighten the academic record. In making this decision the Editorial Board follows COPE's Retraction Guidelines. Aim is to promote the circulation of scientific research by offering an ideal research publication platform with due consideration of internationally accepted standards on publication ethics. The Editorial Board would like to extend i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 25 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…This finding is consistent, however, with the suggestion that secular trends do not reduce the average aerobic fitness of westernized children (Santuz et al, 1997). Kathiresan et al (2010) shown that the less fit asthmatic children were able to normalize their aerobic fitness with a supervised training programme without clinical complications. Their ability to improve aerobic capacity was not related to clinical and spirometric severity before training.…”
Section: Aerobic Training Programmesupporting
confidence: 79%
See 1 more Smart Citation
“…This finding is consistent, however, with the suggestion that secular trends do not reduce the average aerobic fitness of westernized children (Santuz et al, 1997). Kathiresan et al (2010) shown that the less fit asthmatic children were able to normalize their aerobic fitness with a supervised training programme without clinical complications. Their ability to improve aerobic capacity was not related to clinical and spirometric severity before training.…”
Section: Aerobic Training Programmesupporting
confidence: 79%
“…According to , despite the possible benefits of inspiratory resistive breathing training, this mode of exercise's current use in asthmatics is presently insufficient and its clinical benefits not yet justified. Kathiresan et al (2010) evaluated the effect of a supervised aerobic training programme on the cardio respiratory fitness and clinical indicators of control in a group of children with moderate to severe but stable asthma. The degree of response to training and the positive effect on the clinical management were strongly influenced by the level of fitness in the initial evaluation; beneficial effects were shown only in the less fit patients.…”
Section: Inspiratory Resistive Breathing Trainingmentioning
confidence: 99%
“…Children with bronchial asthma, especially those with more severe symptoms, tend to have a sedentary lifestyle and therefore lower cardiorespiratory aerobic capacity than healthy children. 1 Fear to dyspnea and an induced asthma attack inhibits participation in the physical-sports activity of many children. 2 All this, causes a deterioration of physical condition 3 and a lower capacity for physical work in relation to healthy children.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, children with asthma, especially those with a more severe clinical disease, tend to have a sedentary lifestyle and therefore a lower aerobic capacity than in healthy children (Kathiresan & Paulraj, 2010). Fear of breathlessness and induced asthma attacks inhibits participation in physical activity and sport in many patients (Welsh, Kemp, &Roberts, 2005).…”
Section: Introductionmentioning
confidence: 99%